Introducing isotonic fluids into pediatric oncology. (6th May 2022) - Heinz, Amadeus T.; Eichholz, Thomas; Queudeville, Manon; Hartmann, Ulrike; Ott, Alexandra; Heinzel, Oliver; Handgretinger, Rupert; Ebinger, Martin
Abstract: Objective: Hypotonic fluids are commonly used in pediatric oncology despite evidence that these fluids can lead to hospital-acquired hyponatremia. This practice is most likely due to lack of data evaluating risks and benefits of isotonic fluids in pediatric oncology. To address this issue, our study investigates the effects of exchanging hypotonic fluids with isotonic fluids in a large pediatric oncology unit. Study Design: Prevalence of laboratory disorders before and after the change to balanced, isotonic fluids for all patients are compared in this retrospective analysis. Disturbances in electrolyte levels, fluid-, acid-base balance and kidney function were examined. Results: The rate of hyponatremia was reduced using isotonic fluids. There were no hypernatremic events. Volume overload might increase the use of furosemide when using isotonic fluids. Potassium and bivalent cation levels increased. The risk of acidosis is greatly reduced, whereas alkalosis was more frequent due to furosemide use. The rate of acute kidney injury did not increase. Conclusion: Using isotonic fluids for hyper-hydration in pediatric oncology lead to a modest reduction of hospital-acquired hyponatremia without causing hypernatremia, but the effects on fluid balance need further investigation. The additional intake of bivalent cations and buffering anions in balanced fluids has measurable effects.